Sports activities and their relationship to mental health and academic achievement among children with autism spectrum disorder from the point of view of specialists - Mersal, Mersal Abdullah Suleiman (Journal of Educational and Psychological Sciences, 2025)
The study aimed to reveal the relationship between sports activities, mental health, and academic achievement among children with autism spectrum disorder from the point of view of specialists. The researcher used the descriptive approach, and the study sample consisted of (150) who were selected using a purposive sampling method, and the questionnaire was used as a tool to collect data on the subject of the study. The results showed that the overall degree of the impact of sports activities on the psychological health and academic achievement of students with autism spectrum disorder was with an arithmetic mean (3.86), to a large degree, and that there was a statistically significant correlation at the significance level (α = 0.05) between The impact of sports activities, mental health and academic achievement, and the presence of statistically significant differences at the significance level (α = 0.05) between the averages of the responses of the study sample members due to the gender variable in all fields of study and the total score in favor of females, and the absence of statistically significant differences at the significance level (α = 0.05) between the averages of the responses of the study sample members due to the variables of academic qualification and years of experience in all fields of study and total degree. The study recommends enhancing the role of sports activities in increasing the academic achievement of students with autism spectrum disorder, paying attention to sports activities that improve the psychological health of students with autism spectrum disorder, and allocating a staff specialized in sports activities to train students with autism spectrum disorder.